Development Worksheet Integrated PhET Simulation to Improve Critical Thinking Skills in Junior High School - Rahmat*, Anggi Datiatur; Wilujeng, Insih; Kuswanto, Heru; Mat Daud, Anis Nazihah; Saepuzaman, Duden (Jurnal Pendidikan Sains Indonesia, 2024)
Integrating technology has a positive impact on science learning. Technology multiplatform can be used as a didactic tool is physics education technology (PhET). This study aims to develop worksheet integrated PhET simulations. The development adopted the 4D model. The designed activity aims to engage students in critical thinking. The instrument for measuring critical thinking consists of 5 questions based on the critical thinking aspect: interpretation, analysis, evaluation, inference, and explanation. Content and media experts and two practitioners validated the media. The validation result shows a V index between 0.80 - 1.00 for all aspects with very high categories. The readability test was administered to 20 students and gained very good results. The effectiveness test was conducted on two different classes. The experiment class uses a worksheet integrated PhET, while the control class uses a worksheet without PhET. Students in the experiment class had higher critical thinking skills scores than those in class control. It can be interpreted that using worksheet-integrated PhET affected students' critical-thinking skills. The results of this study can be used as a reference for integrating technology into science learning